Pengaruh Kemudahan Penggunaan, Kepercayaan Konsumen dan Ulasan Terhadap Minat Beli Ulang Platform Shopee: Studi Kasus pada Gen Z di Jabodetabek - Rindu Islamia; Afif Zaerofi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the influence of ease of use, consumer confidence, and reviews on repurchase interest on the Shopee platform among Generation Z in the Jabodetabek area. Titled "The Influence of Ease of Use, Consumer Confidence, and Reviews on Repurchase Interest on the Shopee Platform: A Case Study on Gen Z in Jabodetabek," this research employs a causal quantitative approach using the SEM-PLS analysis technique. The sampling method used is purposive sampling, with data collected through an online questionnaire distributed via Google Forms to 150 active Shopee users from Gen Z. The findings of this study are expected to provide insights into the factors influencing repurchase decisions in e-commerce, particularly among young consumers.